The Learning Patterns of Self Regulated Learning in Increasing Achievement of Recipient Students KIP Scholarship Period 2020/2021 PAI Program Faculty of Tarbiyah IAIN Bone - Siddik, Hasbi; Ishak, Ishak (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research discusses the problem of self-regulated learning for the student achievement of KIP scholarship recipients for the 2020/2021 period of the Islamic Education Study Program, Faculty of Tarbiyah IAIN Bone. The objectives of this research are to identify self-regulated learning, to identify the efforts to improve academic and non-academic achievement, and to identify barriers that affect academic and non-academic achievement. This research uses a research methodology, namely the type of research that uses qualitative research to describe an event. The research approaches are sociological, pedagogical, and psychological approach. The data collection methods include observation, interview, and documentation. The data collection and analysis techniques used are data collection as well as data display, data reduction, and data triangulation. The results of self-regulated learning of the students in improving academic and non-academic achievements show that the first uses three aspects, namely aspects of metacognition with repetition, elaboration, and organizational strategies. The second, the self-elaboration aspect, includes extrinsic self-talk, relative ability, and situational interest enhancement. The third is the barriers. There are two factors: internal factors, including physical factors (intelligence), physical factors (attitude and psychomotor), and external factors, including family/parents, lecturers, and other activities.